Development of Lysosome‐Targeted Fluorescent Probes for Cys by Regulating the Boron‐dipyrromethene (BODIPY) Molecular Structure. Issue 48 (1st August 2019) - Gao, Jinhua; Tao, Yuanfang; Zhang, Jian; Wang, Nannan; Ji, Xin; He, Jinling; Si, Yubing; Zhao, Weili
Abstract: Our previous discovery suggested that substituents on the 1, 7 positions delicately modulate the sensing ability of the meso ‐arylmercapto boron‐dipyrromethene (BODIPY) to biothiols. In this work, the impact of delicate modulations on the sensing ability is investigated. Therefore, 1, 7‐dimethyl, 3, 5‐diaryl substituted BODIPY is designed and developed and its conformationally restricted species with a meso ‐arylmercapto moiety (DM‐BDP‐SAr andDM‐BDP‐R‐SAr ) as selective fluorescent probes for Cys. Moreover, the lysosome‐target probes (Lyso‐S andLyso‐D ) based onDM‐BDP‐SAr carrying one or two morpholinoethoxy moieties were developed. They were able to detect Cys selectively in vitro with low detection limits. BothLyso‐S andLyso‐D localized nicely in lysosomes in living HeLa cells and exhibited red fluorescence for Cys. Moreover, a novel fluorescence quenching mechanism was proposed from the calculations by density functional theory (DFT). The probes may go through intersystem crossing (from singlet excited state to triplet excited state) to result in fluorescence quenching. Abstract : Fluorescent probes for Cys : The impact of substituents on the 1, 7‐positions of the meso ‐arylmercapto boron‐dipyrromethene (BODIPY) is investigated.DM‐BDP‐SAr, carrying one or two morpholinoethoxy moieties, turned out to be a preferred probe for Cys with a faster reaction rate. The probe was further modified with a lysosomal‐targeting morpholine moiety to giveLyso‐S andLyso‐D as selective probes for Cys detection in lysosomes (see figure).